Trends and Innovations in Tourism Marketing Within Government Policy - Musa, Hussein Gibreel; Garad, Askar; Mussa, Mahmoud (Universitas Bojonegoro, 2024)
This bibliometric study explores the trends, innovations, and the impact of government policies on tourism marketing from 2000 to 2023. The analysis identifies significant shifts, such as the transition to digital marketing, the rise of experiential and sustainable tourism marketing, and the crucial role of government interventions. Technological advancements, including artificial intelligence, virtual reality, and big data analytics, have significantly enhanced tourism marketing strategies. The COVID-19 pandemic further accelerated the adoption of digital platforms and responsive policy-making. Top-cited articles emphasize sustainability, economic impacts, and health tourism, highlighting influential contributions from leading researchers. Geographical analysis shows that the United States, United Kingdom, and Australia are the most prolific contributors, with emerging markets like India, China, Indonesia, and South Africa also playing vital roles. The findings underscore the dynamic, interdisciplinary nature of tourism marketing research and the essential interplay between marketing strategies and government policies. This study provides a foundation for future research and informs effective policy-making and marketing strategies to enhance the sustainability and competitiveness of the global tourism industry.